Tinjauan Yuridis Aplikasi Sistem Keuangan Desa di Kabupaten Gowa - Ahmad Zulfikar; Kasjim Salenda (Law Department, Universitas Islam Negeri Alauddin Makassar, 2022)
The law provides a more certain guarantee that each village will receive funds from the government through the State and Regional Budgets, which are many times higher, far above the amount currently available in the village budget. The village budget distributed from the center has recently been misused because of the lack of understanding by village officials in managing the budget. So that the budget that had been expected to be used to advance the village was misused by certain elements. In order for the Village Fund Budget (ADD) to achieve the desired goals and be realized properly, in accordance with the mandate of the Law, of course, a planning mechanism, distribution, use, reporting and accountability and supervision of Village Fund Allocation is needed. This has prompted the government together with the Ministry of Home Affairs and BPKP to encourage accountability for village financial management by developing village financial management applications through the village financial system (Siskeudes). The Village Financial System (Siskeudes) application was developed jointly between the Financial and Development Supervisory Agency (BPKP) and the Ministry of Home Affairs (Kemendagri). How to Manage Finance Using the Siskeudes Application Based on Legislation and the Effectiveness of Village Financial Management Using the Application.